The best kept secret in Sports : The 2010 Youth Olympic Games - Judge, L. W.; Petersen, J.; Lydum, M. (International Review for the Sociology of Sport, 2009)
The International Olympic Committee seeks to reignite interest in Olympic sports in a generation of adolescents that are becoming increasingly overweight and inactive. International Olympic Committee president, Jacques Rogge, helped develop a plan for an Olympic Games for teenagers in 2010; the IOC general assembly approved the idea. But since its declaration on 6 July 2007 this new proposal has provoked loyal advocates and equally committed critics. This study examines the level of awareness of this event in the sporting community in the United States. This newly passed initiative will be examined for academic scrutiny from its very infancy, tracing and predicting impact and outcome from the perspective of athletes, coaches, parents and local and national sport officials in the United States.